Psychosocial Risk Factors for Child Welfare among Postpartum Mothers with a History of Childhood Maltreatment and Neglect - Koenig, A. M. (Geburtshilfe Frauenheilkd, 2016)
Background: Childhood maltreatment (CM) can increase the risk of psychosocial risk factors in adulthood (e. g. intimate partner violence, financial problems, substance abuse or medical problems). The transition to parenthood presents those affected by CM with particular challenges, in addition to usual birth-related stressors. Methods: In this cross-sectional study a total of 240 women were interviewed in the puerperium with respect to CM experiences, using the German version of the Childhood Trauma Questionnaire (CTQ). Current psychosocial risk factors (e. g. financial concerns, maternal mental illness, single parent) were assessed using the Constance Index (KINDEX) for early childhood risk factors. Associations between CM experience and psychosocial risk factors were calculated using simple correlation. Results: The average age of participants was 33 years. On the CTQ 13.8 % of participants reported emotional abuse, 6.7 % physical abuse and 12.5 % sexual abuse, while 32.1 % reported emotional neglect and 7.5 % physical neglect during childhood. With rising severity of CM, more psychosocial risk factors (KINDEX) were present. Conclusions: This study shows a clear association between experiences of maltreatment during childhood and the presence of psychosocial stressors among women in the puerperium. Regular screening for a history of CM and parental psychosocial stressors should be conducted early, i.e. during pregnancy, to avoid negative consequences for the child.